Entre crônicas : desenvolvendo a compreensão leitora - Santos, Sílvia Souza (2016)
Both the acquisition of reading and the development of comprehension are fundamental in order for individuals to have autonomy in literate societies. And if we intend to contribute to students’ formation, it therefore becomes necessary to develop and increase these competences. This research report aims to present a new pedagogic intervention proposal for reading a literary text whose product is a Pedagogic Notebook. This research is an attempt to make interactive reading and inference construction viable in order for students to develop reading skills and broaden their comprehension. This paper contains the research sources which substantiate the didactic proposal, a summary of the procedure Didactic Sequencing, the actions which consolidated the proposed strategies, the final considerations and its references. The aim is to promote the development and the improvement of the students’ textual comprehension from reading the literary text, as literature contributes to one’s maturing process, helping us to say the world and say ourselves (COSSON, 2006). The sugges ted strategies justify themselves for the fact that the contemporary educational context demands the formation of proficient readers who are not limited to the text surface when building the text meanings, but who build meanings and mobilize a set of knowledge, in diverse linguistic communicating situations. This proposal has the studies of COSSON (2006), DELL’ISOLA (2001), KLEIMAN (2000a; 2000b), KOCH & ELIAS (2006), LEFFA (1996), MARCUSCHI (2008), SOLÉ (1998), among others as theoretical basis. The intervention occurred in a 7th grade group and its results demonstrated that creating opportunities in which students actively participate in the building of text meanings, use their previous knowledge and experiences to formulate hypothesis, reflect about the texts form and content in order to justify their own points of view, build inferences which are necessary to textual comprehension is strongly positive. At first, the theoretical aspects which support the proposal are explained; then, it presents the research proposing and how the basic sequence execution was mediated and at last, the intervention results are analyzed. The Leitura, interação, compreensão! notebook brings orientations as for developing the present intervention proposal.